PARSING AMBIGUOUS RELATIVE CLAUSES IN L2 ENGLISH: LEARNER SENSITIVITY TO PROSODIC CUES. Issue 1 (25th March 2021) - Goad, Heather; Guzzo, Natália Brambatti; White, Lydia
Abstract: We investigate effects of prosodic cues on interpretation of ambiguous sentences containing relative clauses (RCs) in English by Spanish-speaking learners. English and Spanish differ in default preference for RC attachment: English has a weak low attachment (LA) preference (RC modifies NP2); Spanish has a stronger high attachment (HA) preference (RC modifies NP1). We conducted an interpretation task with auditorily presented stimuli to examine whether prosodic cues determine attachment. Target items were manipulated for position of break and length of RC, NP1, and NP2. For both groups, break and length are significant. For the learners, proficiency interacts with break suggesting L1 transfer: lower proficiency learners choose HA more when break points to LA; higher proficiency learners choose HA more when break points to HA. Lower proficiency learners are more likely to choose LA overall, suggesting a recency effect. Our results confirm the importance of using aural stimuli when testing interpretation of ambiguous sentences.